Wealth, inequality, and sex: The changes in female and male wealth and their consequences for the governance of the Russian Empire from 1700s to 1850s - Elena Korchmina (European Historical Economics Society (EHES), 2023)
Could we measure the contribution of women to the economy in the pre-industrial world? Yes, it is possible, particularly in the context of Russia. By analyzing archival sources, we can not only measure their contribution to the economy but also observe how the Russian Empire evolved into a more economically patriarchal society over time. Examining the distribution of female property across various regions in Russia reveals a significant increase in the share of female property the 18th century, rising from 10% to 40%. However, this growth plateaued and gradually declined. By the late 19th century, the presence of women among top landowners continued to decrease. This substantial surge in female property ownership during the 18th century occurred primarily due to the increasing frequency of women being designated heirs. Using the unique datasets, I assessed the gender gap in wealth and income, which averaged around 25% across provinces. This indicates that the equal access to property established in 1715 led to Russia becoming a relatively gender-equal country over the following century. Consequently, noblewomen in the Russian Empire gained proxy voting rights. Interestingly, the authorities granted this fundamental civil right independently, without significant societal debate on the 'female question'.
Keywords: N00; N13; N33; J16; D63; 330; Russian Empire; Gender; Wealth; Income; Pre-Industrial World